The impact of enterprise systems on corporate performance: A study of ERP, SCM, and CRM system implementations - Hendricks, Kevin B.; Singhal, Vinod R.; Stratman, Jeff K. (Journal of Operations Management, 2007)
AbstractThis paper documents the effect of investments in Enterprise Resource Planning (ERP), Supply Chain Management (SCM), and Customer Relationship Management (CRM) systems on a firm's long‐term stock price performance and profitability measures such as return on assets and return on sales. The results are based on a sample of 186 announcements of ERP implementations, 140 SCM implementations, and 80 CRM implementations. Our analysis of the financial benefits of these implementations yields mixed results. In the case of ERP systems, we observe some evidence of improvements in profitability but not in stock returns. The results for improvements in profitability are stronger in the case of early adopters of ERP systems. On average, adopters of SCM system experience positive stock returns as well as improvements in profitability. There is no evidence of improvements in stock returns or profitability for firms that have invested in CRM. Although our results are not uniformly positive across the different enterprise systems (ES), they are encouraging in the sense that despite the high implementation costs, we do not find persistent evidence of negative performance associated with ES investments. This should help alleviate the concerns that some have expressed about the viability of ES given the highly publicized implementation problems at some firms.